Montreal Protocol's impact on the ozone layer and climate ... - Egorova, Tatiana; Sedláček, Jan; Sukhodolov, Timofei; Karagodin-Doyennel, Arseniy; Zilker, Franziska; Rozanov, Eugene (ETH Zurich, 2023)
It is now recognized and confirmed that the ozone layer shields the biosphere from dangerous solar UV radiation and is also important for the global atmosphere and climate. The observed massive ozone depletion forced the introduction of limitations on the production of halogen-containing ozone-depleting substances (hODSs) by the Montreal Protocol and its amendments and adjustments (MPA). Previous research has demonstrated the success of the Montreal Protocol and increased public awareness of its necessity. In this study, we evaluate the benefits of the Montreal Protocol on climate and ozone evolution using the Earth system model (ESM) SOCOLv4.0 (modeling tools for studies of SOlar Climate Ozone Links) which includes dynamic modules for the ocean, sea ice, interactive ozone, and stratospheric aerosol. Here, we analyze the results of the numerical experiments performed with and without limitations on the ozone-depleting substance (ODS) emissions. In the experiments, we have used CMIP6 (Coupled Model ... : Atmospheric Chemistry and Physics, 23 (9) ...